Geochemical and Nd isotopic constraints on provenance and depositional setting of the Shihuiding Formation in the Shilu Fe–Co–Cu ore district, Hainan Province, South China. (1st April 2016) - Yu, Liangliang; Zou, Shaohao; Cai, Jianxin; Xu, Deru; Zou, Fenghui; Wang, Zhilin; Wu, Chuanjun; Liu, Meng
Highlights: Shihuiding Formation shows banded iron structure. Baoban Group was suggested to be the provenance of Shihuiding Formation. Provenance modeling quantitatively constrained the contribution of the provenance. The metallogenic material of Fe in Shihuiding Formation was derived from seafloor-derived reducing hydrothermal solutions. Shihuiding Formation deposited in the passive margin. Abstract: The Shihuiding Formation, a subordinate succession hosting the Fe–Co–Cu ores, is a suite of Neoproterozoic terrigenous clastic rocks occurring in the Shilu Fe–Co–Cu ore district of the Hainan Island, South China. Integrated petrographical, geochemical, and Nd isotopic analyses have been carried out on 23 sandstone specimens of the Shihuiding Formation in order to understand their provenance and the tectonic setting of their deposition. The samples can be divided into two groups, quartzose sandstones (13 samples) and ferruginous sandstones (10 samples). The ferruginous sandstones have average SiO2 and Fe total contents of 77.23 wt.% and 18.09 wt.%, respectively, and this contrasts with the higher average SiO2 (94.04 wt.%) and lower Fe total (2.67 wt.%) contents of the quartzose sandstones. The bivariant Th/Sc and Zr/Sc ratios indicate a predominantly recycled sedimentary provenance, and the low to medium degrees of weathering are commonly indicated by an average chemical index of maturity (CIM) of 81 and an average chemical index of alteration (CIA) of 68. The Shihuiding Formation sandstones have REE contents of 21–249 ppm, with LREE/HREE = 9.18 and δEu = 0.67. The ε Nd (970 Ma) values of −5.7 to −3.4, and model ( T DM ) ages of 2099–1773 Ma are compatible with a source mainly from the Paleo- to Mesoproterozoic Baoban Group, a suite of metamorphosed sedimentary rocks intruded by ca. 1450 Ma granites. Quantitative provenance modeling indicates that the Shihuiding Formation sandstones are best modeled with a mixture of 29% plagioclase–amphibole gneiss (29 P), 38% quartz–muscovite schist (38 Q), and 33% granite (33 G) detritus. Mixing the ε Nd values of the sandstones, calculated at 970 Ma, indicates that the sediment received 22–47% (average 34%) of its detritus from the Baoban Group quartz–muscovite schists. Components from hydrothermal fluids may also have been involved during deposition of the Shihuiding Formation sandstones, as revealed by a bivariant Al/(Al + Fe + Mn) vs. Fe/Ti plot, positive Eu anomalies, and negative Y anomalies relative to PAAS. Tectonic discrimination diagrams, such as La–Th–Sc and Th–Co–Zr/10, indicate a passive continental margin setting for the deposition of the Shihuiding Formation. In terms of its geological setting, we propose that the Shihuiding Formation was deposited in a peripheral foreland basin, supplied by detritus shed from the Grenville Orogenic Belt during the assemblage of the Rodinia Supercontinent.